Behaviors of Yahisuli’s Parents in Early Childhood Immunization in 2018 - Ependja, Antoine Towaka; Baelo, Vif Foyo; Baombolia, Zenon Lokangu (Open Science Journal, 2021)
This descriptive cross-sectional study aims to determine factors associated with Yahisuli's parents' behaviors in early childhood immunization in 2018. To collect data, we used a questionnaire administered to a non-probability convenience sample of 96 parents of children 0-11 months of age. Descriptive analysis allowed us to compare our results with previous work. We recorded an average age of 32.8 years and a male/female sex ratio of 1.3. More than 95% of the parents went to school, of which 58.5% have a high school education. The birth rank of the last child ranged from 3 to 5 with a sex ratio of 1.3 in favor of males. Nearly 15% of children have not been fully vaccinated. In this work, 55 out of 96 parents bring their children to a health facility to be vaccinated to ensure their protection (76.4%) and prevention against infectious diseases (47.3%). On the other hand, 42% do not adhere to vaccination because of ignorance, fear due to children's incessant crying after vaccination, adverse post-immunization events. When it came to vaccines, several misunderstandings were raised. These corroborate rumors observed under other skies. Thus, a descriptive and analytical study on the epidemiological surveillance of adverse effects of vaccines is indispensable in the province of Tshopo.